2015
DOI: 10.5505/tjb.2015.24085
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Aprotinin on the preanalytical stability of adrenocorticotrophic hormone

Abstract: Objective: The susceptibility of plasma adrenocorticotropic hormone (ACTH) to enzymatic degradation has limited the stability of ACTH. Many non-routine tests require the collection of blood on special proteinase inhibitor cocktails to preserve the integrity of the sample. This may provide benefits in sample collection and routine clinical practice. This study examined if a proteinase inhibitor, aprotinin, mixed with blood at the time of collection, would change the stability of ACTH in plasma at various temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous investigations in humans 30,31 and dogs 23,29 have suggested that the use of aprotinin, a protease inhibitor, may help prevent ACTH proteolytic degradation after sample collection. In our study, plasma ACTH values in the presence and absence of aprotinin were not significantly different in the three sets of samples analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations in humans 30,31 and dogs 23,29 have suggested that the use of aprotinin, a protease inhibitor, may help prevent ACTH proteolytic degradation after sample collection. In our study, plasma ACTH values in the presence and absence of aprotinin were not significantly different in the three sets of samples analysed.…”
Section: Discussionmentioning
confidence: 99%
“…28 In clinical practice, however, this procedure may present logistical problems because samples for plasma ACTH measurement are frequently shipped to an external laboratory. Therefore, an additional aim of the present study was to determine if aprotinin, a protease inhibitor previously investigated for use in human and canine samples, 23,2931 may help prevent ACTH degradation in feline plasma samples.…”
Section: Introductionmentioning
confidence: 99%